Emerging from the Euro Debt Crisis : making the single currency work - Heise, Michael (Springer Berlin Heidelberg, 2013)
Despite the success of policymakers and the European Central Bank in calming down financial markets since the summer of 2012, European leaders are still facing formidable challenges in making the single currency work in a complex environment. This book starts with a review of the necessary elements of a currency union and highlights the reasons why the system has run into its present troubles. It points to important policy recommendations to be drawn from a structural analysis of the currency union, achievements and failures of the currency union and ways to improve fiscal sustainability and arrive at stable macroeconomic performance for the union. It highlights the importance and the effectiveness of structural reforms that have to accompany fiscal consolidation and discusses the appropriate tools of crisis management and why a restructuring of the Eurozone is not the right step. Based on these considerations, a long-term target picture for the Eurozone as a part of the EU is outlined, providing a valuable contribution to a hopefully intense public debate in the coming years. "This book makes the case for European monetary union, calling for closer integration but doing so in a meaningful and well reflected way. Improvements are discussed how to make the Euro work on a sustainable basis. Besides a credible commitment of all Euro members to fiscal discipline, the issue of macroeconomic stability and structural reforms needs to be highlighted. Errors in policy making after inception of the Euro are at the heart of the disruptions of recent years. For the future, the author shows the ways and means how more stability could be achieved, including the possibilities of a euro exit and sovereign defaults. This book is written by a highly competent author. Based on a thorough analysis it presents a lucid  interpretation of a complex situation. Highly recommendable read." Prof. Dr. Dr. h.c. mult. Otmar Issing, President, Center for Financial Studies (CFS), House of Finance, Goethe University Frankfurt; Former board member and chief economist of the ECB and the Deutsche Bundesbank